A Novel UHPLC Method for the Determination of Amino Acids using either Fluorescence or Ultraviolet Detection - Fiechter, Gregor; K. Mayer, Helmut (Current Analytical Chemistry, 2014)
A new UHPLC protocol for the determination of amino acids after pre-column derivatization with 6- aminoquinolyl-N-hydroxysuccinimidyl carbamate (AQC) was presented. Applying a simple and easy to prepare binary eluent system, the 20 major proteinogenic amino acids were separated in about 7 min with a total runtime of 10.5 min until the next injection. Since AQC amino acid derivatives were primarily designed to be used with fluorescence detection but facilitate UV detection as well, both approaches were evaluated for their applicability with the established UHPLC method. 6-aminoquinoline, the hydrolysis by-product of derivatization which implies similar absorbance as amino acid derivatives, was effectively separated prior to the polar amino acids, hence no interferences in UV detection were observed. For UV detection at 254 nm, all amino acids exhibited a quite similar response, whereas the respective fluorescence yield at 395 nm emission (excitation at 245 nm) indicated significant dependencies from the applied conditions mainly affected by aqueous quenching. Regarding the possible sensitivity compared to UV, fluorescence detection proved to be superior with detection limits ranging down to the low fmol level. Additionally, the established method was successfully applied to analyze amino acid levels intrinsic to commercial hydrolysates/peptones, that were primarily destined for microbiological use. The found proportion of amino nitrogen ranged from 8% for soy protein acid hydrolysate to 2% for fish peptone, while both detection approaches proved to be equally suitable for the given application.
Keywords: hydrolysate